Ecological and Socio-Economic Contribution of Mt. Elgon Forest Park, Eastern Uganda - Buyinza Mukadasi (Jurnal Ilmu Kehutanan, 2010)
This paper explores the ecological and socio-economic contribution of Mt. Elgon forest park, eastern Uganda. An effort was taken to evaluate the importance of Mt. Elgon forest park resources to the local people by using the local plant knowledge to value the forest park resources. An integrated approach of participatory rural appraisal (PRA), Participatory Resource Valuation (PRV), household survey, group discussions and forest walks were conducted during the months of June to December, 2008 in Mutushet and Kortek Parishes, Kapchorwa District. Using random sampling methods, 120 respondents were selected and interviewed. Ten forest uses were identified with the highest dependence being in the supply of timber for income and domestic building poles, the latter having the highest average annual household value of UGx. 67919 (US$37). The forest use most valued in both Mutushet and Koterk was medicine with an average annual household value of UGx. 60,371 (US$ 33) and UGx. 75,464 (US$ 42) respectively. The forest provision of medicine, domestic building materials, soil conservation, bush meat, charcoal and timber was more valued in Koterk, while provision of firewood, honey and pasture were more valued in Mutushet. The forest’s provision of food was valued equally in the two areas with an average annual value of UGx. 30,186 per household. Forest park resources accounted for 55% of the household income. Participatory valuation approaches are ecommended for estimation of forest park resources’ value in a non-cash economy.